Emerging Innovations and Clinical Perspectives in Dental Implantology: A Contemporary Review (Academia Journal of Medicine, 2026)
Dental implants have become a reliable and widely accepted treatment option for replacing missing teeth. Continuous advancements in biomaterials, implant design, digital technologies, and regenerative procedures have significantly enhanced the predictability and long-term success of implant therapy. Modern developments such as surface modification techniques, computer-guided implant placement, and biologically active coatings have improved osseointegration and treatment outcomes. Furthermore, digital workflows and advanced imaging techniques allow clinicians to plan and execute implant procedures with greater accuracy. Despite these improvements, complications such as peri-implant diseases and the need for long-term clinical evidence remain important concerns. This review discusses contemporary advancements in dental implantology and highlights potential future directions aimed at improving patient care and clinical success.
Keywords: Implant; Innovation; Digital Dentistry